CONTENT ANALYSIS OF READER COMMENTS ABOUT COVID-19 ON MEDIA AGGREGATOR LINE TODAY - Joe Harrianto Setiawan; Cintia Caroline; Deddy Muharman (ASPIRATION Journal, 2021)
In the development of communication industry, mass media have evolved and brought the existence of a news aggregator. In Indonesia, a Japanese-based instant messaging apps company has expanded its platform to news aggregator named LINE Today. LINE Today allow their users to share their feedback regarding to the presented news as comments, and narrowed feedback can create the public opinion. In the midst of the Covid-19 pandemic the news outlet is currently tinged with news about it. This research would like to explore how the public opinion of Indonesian about Covid-19 through the news comments in LINE Today. With quantitative content analysis method, the most commented news about Covid-19 in LINE Today constructed with three kinds of feedback trigger and three determinants of public opinion. The result has shown that the Covid-19 news comments in LINE Today are mostly triggered by the relationship between the commentator and the news subject. Indonesian public opinions regarding to the news about Covid-19 in LINE Today Indonesia are mostly determined by their belief not by fact.